Urinary Excretion of Zinc After Taking Long Term Use of Hormonal Contraceptives - Rahman, Mansura; Hai, MA; Begum, Noorzahan; Tarafdar, SA; Akther, Sohela; Banu, Shahanara (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll ?Volume 2 Number 2 December 2010 ? Page 6-7 DOI: http://dx.doi.org/10.3329/jssmc.v2i2.12045